2018
DOI: 10.1038/s41598-018-29956-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased moral condemnation of accidental harm in institutionalized adolescents

Abstract: Social deprivation, as faced by children in institutional rearing, involves socio-cognitive deficits that may persist into adolescence. In particular, two relevant domains which prove sensitive to pre-adult neurodevelopment are theory of mind (ToM) and moral judgment (a complex skill which partially depend upon ToM). However, no study has assessed moral evaluation in adolescents with a history of institutional care, let alone its relationship with ToM skills. The present study aims to bridge this gap, focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
2
7
0
1
Order By: Relevance
“…Although we targeted a particular sample of Colombian AOs, our sample shared demographic factors, and the profile of offenses to samples assessed in previous studies (Brazil et al, 2013; Zou et al, 2013; Vilà-Balló et al, 2015), including reports assessing specific cognitive, emotional, and socio- cognitive processes (see Gonzalez-Gadea et al, 2014; Baez et al, 2018a). In fact, the AOs tested herein resembled those of previous samples from other countries in terms of demography (sharing sex, ages, socio-cultural background), behavioral disturbances (including months of jail and relapses), and type of offenses (including offenses such as homicide, sexual related offences, extortion among other offenses; see Brazil et al, 2013; Zou et al, 2013; Vilà-Balló et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although we targeted a particular sample of Colombian AOs, our sample shared demographic factors, and the profile of offenses to samples assessed in previous studies (Brazil et al, 2013; Zou et al, 2013; Vilà-Balló et al, 2015), including reports assessing specific cognitive, emotional, and socio- cognitive processes (see Gonzalez-Gadea et al, 2014; Baez et al, 2018a). In fact, the AOs tested herein resembled those of previous samples from other countries in terms of demography (sharing sex, ages, socio-cultural background), behavioral disturbances (including months of jail and relapses), and type of offenses (including offenses such as homicide, sexual related offences, extortion among other offenses; see Brazil et al, 2013; Zou et al, 2013; Vilà-Balló et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as recently proposed by Hirschfeld-Kroen et al (2021) , Accidental Harm scenarios are an important context for broadening our understanding of the relation between agency and moral judgments thanks to the incongruence between the agent’s intention, which is neutral, and the action’s outcome, which is instead negative ( Young and Saxe, 2009 ). Indeed, for judging these scenarios, people must inhibit a salient and prepotent representation (i.e., the observed outcome for the victim) and assign more weight to a less immediate alternative (i.e., the intention of the agent; Young and Saxe, 2009 ; Margoni and Surian, 2016 , 2021 ; Baez et al, 2018 ; Schwartz et al, 2021 ). Thus, the pattern of correlations that we observed may suggest that people with stronger SoA fail to inhibit outcome/victim-based emotional processes.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for these results is that chronic exposure to negative environments (e.g., violent, drug use, and childhood abuse) may impede the normal developmental trajectories of frontal lobe functions, which leads to maladaptive behaviors. For instance, previous studies demonstrated that institutionalized adolescents raised under social deprivation conditions displayed delayed development in relation to theory of mind (ToM) relative to adolescents raised with their biological families (Baez et al, 2018). This finding implied that the development of moral cognition is vulnerable to the impact of institutionalization.…”
Section: Atypical Cognitive and Frontal Lobe Functions In Adolescent ...mentioning
confidence: 99%